Home range, movement, and distribution patterns of the threatened dragonfly Sympetrum depressiusculum (Odonata: Libellulidae): a thousand times greater territory to protect - Dolný, Aleš; Harabiš, Filip; Mižičová, Hana (PLoS One, 2014)
Dragonflies are good indicators of environmental health and biodiversity. Most studies addressing dragonfly ecology have focused on the importance of aquatic habitats, while the value of surrounding terrestrial habitats has often been overlooked. However, species associated with temporary aquatic habitats must persist in terrestrial environments for long periods. Little is known about the importance of terrestrial habitat patches for dragonflies, or about other factors that initiate or influence dispersal behaviour. The aim of this study was to reveal the relationship between population dynamics of the threatened dragonfly species Sympetrum depressiusculum at its natal site and its dispersal behaviour or routine movements within its terrestrial home range. We used a mark-release-recapture method (marking 2,881 adults) and exuviae collection with the Jolly-Seber model and generalized linear models to analyse seasonal and spatial patterns of routine movement in a heterogeneous Central European landscape. Our results show that utilisation of terrestrial habitat patches by adult dragonflies is not random and may be relatively long term (approximately 3 mo). Adult dragonflies were present only in areas with dense vegetation that provided sufficient resources; the insects were absent from active agricultural patches (p = 0.019). These findings demonstrate that even a species tightly linked to its natal site utilises an area that is several orders of magnitude larger than the natal site. Therefore, negative trends in the occurrence of various dragonfly species may be associated not only with disturbances to their aquatic habitats, but also with changes in the surrounding terrestrial landscape.
Keywords: ohrožené druhy; Female; hustota populace; vážky; Animals; Endangered Species; ženské pohlaví; Česká republika; mužské pohlaví; Male; rozšíření zvířat; Odonata; Population Density; zvířata; Animal Distribution; Czech Republic; ekosystém; Ecosystem